Horsehair Worms, Hairworms, Gordian Worms, Nematomorphs, Gordius spp. (Nematomorpha: Gordioidea) - John L. Capinera (EDIS, 2002)
This document is EENY-117, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 1999.